Nonlinear Robin problems with indefinite potential. (June 2020) - Leonardi, S.; Onete, Florin I.
Abstract: We consider a nonlinear Robin problem driven by the p -Laplacian plus an indefinite potential. The conditions on the source term are minimal. We prove two multiplicity theorems with sign information for all the solutions. In the semilinear case ( p = 2 ), we show that we can have multiple nodal solutions. We apply our results to a special class of logistic equations with equidiffusive reaction.